Field notes and Pam Allen and Reid I. Allen letter to Carl J. Bendorf, December 1, 1988 - Allen, Pamet al; Allen, Reid I.et al (1988)
List of birds and locations contributed by Pam Allen and Reid I. Allen. Included with the field notes is a letter from Pam Allen and Reid I. Allen to Carl J. Bendorf noting this is their first field report for IOU. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of fall 1988. Epson - sheet feed